Augmenting the intertemporal CAPM with inflation: Further evidence from alternative models. (November 2017) - Shi, Qi; Li, Bin; Cheung, Adrian (Wai Kong); Chung, Richard
Studies consistently find that inflation is an important augmented factor for intertemporal capital asset pricing models (ICAPMs) when pricing the Fama–French 25 size and book-to-market portfolios. We extend this line of research by investigating two alternative ICAPM models (from Michel; Hahn and Lee) and the three-factor model from Hou et al. We find significant evidence that both ICAPMs and Hou et al.'s three-factor model perform better when augmented with inflation than the original models. The augmented models achieve a good model fit with the fewest factors, thus avoiding or alleviating the over-fitting problem.